Eigil Greve Knuth, 1903-1996 - Laursen, Dan (ARCTIC, 1996)
. Count Eigil Knuth was born on 8 August 1903 at Klampenborg, an affluent community 10 km north of Copenhagen, the son of captain Eigil Greve Knuth and Djimphna, nee Gamel. . Knuth was always of an uneasy mind, which was especially visible when he was younger. He graduated from one of Copenhagen's oldest, best, and most distinguished high schools (gymnasium), but instead of attending the university, he continued at a technical school for apprentices to gain admission to the building technique school of the Academy of Fine Arts, where he spent the years from 1922 to 1924. He then moved to Italy for three years to study sculpture. Back in Denmark, he spent a year at Niels Buck's Gymnastic Folk High School and graduated as a gymnastics teacher in the spring of 1932. That same summer, he participated for the first time in the excavating of old Norse ruins in West Greenland, assisting Dr. Aage Roussel from the National Museum. . During the summer of 1934, he was excavating old Norse ruins, this time at Igaliko, again assisting Dr. Roussel and also Dr. Poul Norlund. In 1935 he was archaeologist on the Courtauld Expedition to East Greenland, during which Gunbjorns Fjeld, Greenland's highest mountain, was climbed. There Knuth was assisting Dr. Helge Larsen from the National Museum, and without doubt their discussions had an important impact on Knuth the future archaeologist. . During the Courtauld expedition, Knuth had many talks with Ebbe Munck, in which they agreed that their generation owed the nation a Danish expedition comparable to the Danmark Ekspedition 1906-08. . As soon as the war was over, Knuth and Munck began to organize the contemplated expedition to Peary Land. Paid for by the newly established Danish Expedition Foundation, it would be the first in a long row of Peary Land Expeditions headed by Knuth. . [The expedition house "Bronlund Hus" was built at Bronlund Fjord and from it many sledge and hiking trips were carried out which resulted in many archaeology discoveries.] However, Knuth deserves most ...